Global Processing of Biological Motions - Bertenthal, Bennett I; Pinto, Jeannine (Psychological Science, 1994)
The structure of the human form is quickly and unequivocably recognized from 10 to 13 points of light moving as if attached to the major joints and head of a person walking Recent psychophysical and computational models of this process suggest that these displays are organized by low-level processing constraints that delimit the pair-wise connections of the point lights In the current research, these low-level constraints were rendered uninformative by a masking paradigm The results from four experiments converged to show that the perception of structure in a point-light walker display does not require the prior detection of individual features or local relations